2000
DOI: 10.1002/1521-396x(200011)182:1<239::aid-pssa239>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-Induced Modifications of Trap Parameters in Nanocrystalline Porous Silicon

Abstract: The changes produced by anodic and natural oxidation upon the trap parameters in nanocrystalline porous silicon were compared. To put them in evidence, we used optical charging spectroscopy. The same trapping levels (with the same activation energies) were observed after both oxidation processes. In comparison with fresh samples, a new trapping level (the deepest one) appears and the concentrations of the surface traps strongly diminish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The shoulder positioned at 1100 nm represents the contribution of the Si substrate [ 11 ] and peak located around 1200 nm is due to Ge‐rich SiGe NCs. It is observed that for S FA sample the overall spectral intensity increased almost three times compared to that observed for S AG structures, along with an increase in the relative intensity of the SiGe NCs peak 6 with respect to peaks 1–4 produced by strain and interface, [ 33,34 ] implying residual strain within the structure. For RTA structure, the spectral intensity was reduced to ≈1/4 of that for S AG structure, with a relative increase in peak intensity from the SiGe NCs’ peak 6 with respect to peaks 1–4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shoulder positioned at 1100 nm represents the contribution of the Si substrate [ 11 ] and peak located around 1200 nm is due to Ge‐rich SiGe NCs. It is observed that for S FA sample the overall spectral intensity increased almost three times compared to that observed for S AG structures, along with an increase in the relative intensity of the SiGe NCs peak 6 with respect to peaks 1–4 produced by strain and interface, [ 33,34 ] implying residual strain within the structure. For RTA structure, the spectral intensity was reduced to ≈1/4 of that for S AG structure, with a relative increase in peak intensity from the SiGe NCs’ peak 6 with respect to peaks 1–4.…”
Section: Resultsmentioning
confidence: 99%
“…[27,31] Such an effect has been attributed to the inherently different ramp rate for RTA compared to conventional furnace [30,32] where the interfacial regions are more likely to be affected by annealing. [33] FA produces variation in stress distribution within the structure and thereby affects the NC size and bandgap. It has been argued that in the case of conventional FA, the inherently increased exposure time results in increased NC sizes and stress relaxation accompanied with defects and dislocations, [34] resulting in a deterioration of the optical and electrical properties.…”
mentioning
confidence: 99%